Analysis and Design of Integrated Vehicle and Crew Scheduling System Using GAIA Methodology - Shibghatullah, Abdul Samad; Abdullah, Nazri (2007)
An integrated vehicle and crew scheduling is a complex problem to solve because of the large number of resources that need to be managed, and complexity of rules regarding allocating vehicle and crew shifts. However, there are potential benefits from integrating both scheduling including cost saving in regional area where routes have fewer relief points. The aim of this research is to design the integrated vehicle and crew scheduling system using Multi-Agents System (MAS). The paper presents agents analysis and design using Gaia methodology.